Vegan Diet Is Associated With Favorable Effects on the Metabolic Performance of Intestinal Microbiota: A Cross-Sectional Multi-Omics Study - Prochazkova, Magdalena; Budinska, Eva; Kuzma, Marek; Pelantova, Helena; Hradecky, Jaromir; Heczkova, Marie; Daskova, Nikola; Bratova, Miriam; Modos, Istvan; Videnska, Petra; Splichalova, Petra; Sowah, Solomon A.; et al. (Frontiers in Nutrition, 2022)
Background and Aims Plant-based diets are associated with potential health benefits but the contribution of gut microbiota remains to be clarified. We aimed to identify differences in the key features of microbiome composition and function with relevance to metabolic health in individuals adhering to a vegan vs. omnivore diet. Methods This cross-sectional study involved lean, healthy vegans (n=60) and omnivore (n=33) subjects. We assessed their glucose and lipid metabolism and employed an integrated multi-omics approach (16S rRNA sequencing, metabolomics profiling) to compare dietary intake, metabolic health, gut microbiome, and fecal, serum and urine metabolomes. Results Vegans had more favorable glucose and lipid homeostasis profiles compared with omnivores. Long-term reported adherence to a vegan diet affected only 14.8% of all detected bacterial genera in fecal microbiome. However, significant differences in vegan and omnivore metabolomes were observed. In feces, 43.3% of all identified metabolites were significantly different between vegans and omnivores including amino acid fermentation products p-cresol, scatole, indole, methional (lower in vegans) and polysaccharide fermentation products short- and medium-chain fatty acids (SCFAs, MCFAs), and their derivatives (higher in vegans). Vegan serum metabolome differed markedly from omnivores (55.8% of all metabolites), especially in amino acid composition including low BCAAs, high SCFAs (formic-, acetic-, propionic-, butyric acids) and dimethylsulfone, the two latter being potential host-microbiome co-metabolites. Using machine-learning approach, we tested discriminative power of each dataset. The best results were obtained for serum metabolome (accuracy rate 91.6%). Conclusion While only small differences in the gut microbiota were found between groups, its metabolic activity differed substantially. In particular, we observed a significantly different abundance of fermentation products associated with protein and carbohydrate intakes in vegans. Vegans had significantly lower abundances of potentially harmful (such as p-cresol, lithocholic acid, BCAAs, aromatic compounds etc.) and higher occurrence of potentially beneficial metabolites (SCFAs and their derivatives).